A Comparative Evaluation of Two Delivery Methods for a Work Focused Fatigue Management Intervention for Individuals with Inflammatory Arthritis - Karkon, Shalaleh (Trinity College Dublin. School of Medicine. Discipline of Occupational Therapy, 2025)
ABSTRACT Background: Inflammatory Arthritis (IA) often leads to early work disability, impacting employment and causing socio-economic challenges. Fatigue is a major symptom that affects productivity and increases absenteeism. In Ireland, individuals with IA prefer peer-supported, group-based rehabilitation interventions. The Fatigue Management Education for Work (FAME-W) was developed to meet this need as an in-person group programme. However, due to COVID-19, it was adapted to an online format, and a self-guided workbook was introduced. Methodology: FAME-W's development followed the Medical Research Council framework for complex interventions, ensuring a theoretical foundation and a focus on IA needs. The research aimed to test feasibility and compare delivery methods: an online group-based format and a self-guided workbook. Three studies were conducted: a feasibility study using a comparative randomised controlled trial (RCT) with qualitative components; a multisite comparative RCT to evaluate the impact on work performance; and a mixed methods process evaluation assessing implementation, focusing on fidelity, reach, dose, mechanisms of impact, and context. Results: The feasibility study found both formats acceptable and feasible. Improvements in symptom management and work ability indicated potential for a larger trial. In the comparative RCT, neither format showed statistically significant differences between groups for work performance, fatigue, pain, or quality of life, though slight within-group improvements were seen. The process evaluation highlighted the online format’s interactivity and peer support, while the workbook provided flexibility for self-paced learning. Both methods aided self-management of IA-related fatigue. Conclusion: Both delivery methods effectively support IA symptom management and work performance, warranting further large-scale research to refine intervention strategies.
APPROVED
Keywords: Fatifue; Pain; Mental well-being; Work; Employment; Self-management; Non-pharmaceutical; Intervention; Telehealth; Online intervention; Inflammatory arthritis; Work-related fatigue; Work participation; Goal setting; Self-efficacy; Arthritis and employment; Work-focused intervention; Digital health